From Patients to Platelets and Back Again: Pharmacological Approaches to Glycoprotein VI, a Thrilling Antithrombotic Target with Minor Bleeding Risks - Martins Lima, Augusto; Martins Cavaco, Ana C.; Fraga-Silva, Rodrigo A.; Eble, Johannes A.; Stergiopulos, Nikolaos (Thrombosis and Haemostasis, 2019)
Despite significant advances in the treatment of thrombogenic diseases, antiplatelet therapies are still associated with a high bleeding risk. Consequently, potential benefits of preventing thromboembolic events by pharmacological agents need to be balanced with the potential harm of inducing hemorrhage. Glycoprotein VI (GPVI) is a platelet-specific receptor, which plays a crucial role in thrombus formation. GPVI deficiency has been identified in patients who suffer from significant reduction of collagen-induced thrombus formation, with a slight tendency for mild bleeding. However, an isolated GPVI deficiency can reduce thrombus formation while not resulting in severe bleeding. Together, these observations strongly suggest that physiological hemostasis does not require GPVI, but pharmacological GPVI modulation may provide novel “bleeding-free” antithrombotic therapies. In this review, we discuss recent findings regarding the biological role of GPVI in platelet-related disorders and highlight the efforts to develop potential therapeutic strategies based on its structure, signaling pathways, and biological effects.
Keywords: GPVI; antiplatelet therapy; drug discovery; protein–protein interaction